On the Integration of Generative Artificial Intelligence into the Teaching of Basic Computer Technology Courses in Chinese Universities Application Prospects, Challenges and Countermeasures - Ma, Liang (Journal of Educational Research and Policies, 2025)
With the rapid development of artificial intelligence technology, Artificial Intelligence Generated Content (AIGC) has been widely used in the field of higher education. Generative AI has the ability of self-learning and automatic content generation, which brings unprecedented changes to the teaching method of basic computer technology courses in universities. Starting from the basic concept of generative AI technology, this paper explores the potential application of its integration in basic computer technology courses in universities, analyses the application prospects of generative AI in the areas of teaching content generation, personalized teaching, and automated assessment, and also points out the challenges and problems that may be encountered in the practical application. Finally, this paper puts forward corresponding countermeasures and suggestions, aiming to provide reference and information for university teachers and educational technologists, and to promote the in-depth application of generative AI technology in the field of university computer education.